Ketersediaan Kotak P3K Diperusahaan PT X Berdasarkan Undang- Undang No 1 Tahun 1970 - Lisa Nur Afifah; Achmad Syafiuddin; Pradana Arie (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Workers / laborers are always faced with sources of danger in the workplace that allow work accidents and work-related illnesses to occur. Occupational Safety and Health (K3) requirements as mandated by   Law no. 1 of 1970 concerning occupational safety and health is an important part of K3 protection for workers. With the stipulation of this ministerial regulation, protection for workers who experience accidents at work can be realized through quick and appropriate first aid measures. One of the important aspects regulated in the labor law is the company's obligation to provide occupational health and safety protection to workers. This includes the availability of a first aid kit which must be in the workplace. The research method used in this study is qualitative research in which this study assesses the availability of first aid kits in company X using Law no. 1 of 1970. The survey results obtained, based on law no. 1 of 1970 the PT X company can be said t o be feasible in terms of the availability of first aid within the company.